PREDIKSI TINGKAT DEPRESI REMAJA DENGAN INSULIN DEPENDENT DIABETES MELLITUS (IDDM) DI IKATAN DIABETESI ANAK DAN REMAJA KOTA MALANG - Priasmoro, Dian Pitaloka; Ispriantari, Aloysia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
Predicted levels of depression in adolescents show no depression. Possible affected by longdiagnoses, regular visits to treatment, drug use, and school environment. This study aims to predictdepression rates in adolescents with IDDM in the Association of Child and Rehabilitation Diabetesi(IKADAR) Malang. This research uses descriptive method with sampling technique of totalsampling in 24 parents aged 10-19 years old in IKADAR Malang. The study was conducted inJune-July 2017. The instrument used was the Center for Epidemiological Studies Depression Scalefor Children (CES-DC) which had 20 items with an overall value range of 0-60, with a cut-pointvalue <15 not depressed and> 15 depression. Before the instrument is used to retrieve the datatested the validity with Pearson Correlation Moment Product with r count 1.00> r table 0,549 andreliability Alpha Chronbach's 0.911> r table with df = (10-2). So concluded the instrument validand reliable. After the data collected will be done data processing with the stage of editing, coding,tabulating and statistical analysis. The results of univariate analysis were presented in descriptiveform. The analysis results showed the empirical mean score of depression level 13,79 or notdepression. So it is advisable for adolescents to continue looking for an adaptive environment so asto prevent depression.